THU0721-HPR The effects of upper and lower limb exercise on the microvascular reactivity in systemic sclerosis patients. (12th June 2018) - Mitropoulos, A.M.; Gumber, A.; Crank, H.; Akil, M.; Klonizakis, M.
Abstract : Background: Vascular endothelial injury is one of the early hallmarks in systemic sclerosis (SSc). High intensity interval training (HIIT) is known to improve vascular function in a range of clinical conditions.Ramos et al.., 2015 HIIT in particular has demonstrated improvements in clinical outcomes, in conditions that have a strong macroangiopathic component. Nevertheless, the effect of HIIT on microcirculation in SSc patients is yet to be investigated. Objectives: Therefore, the purpose of the study was to compare the effects of two HIIT protocols (cycle and arm cranking) on the microcirculation of the digital area in SSc patients. Methods: Thirty four SSc patients (65.3±11.6 years old) were randomly allocated in three groups (cycling n=11, arm cranking n=11 and control group n=12). The exercise groups underwent a twelve-week exercise program twice per week. All patients performed the baseline and post-exercise intervention measurements where the physical fitness, functional ability, transcutaneous oxygen tension (ΔtcpO2 ), body composition and quality of life were assessed. Endothelial-dependent as well as -independent vasodilation were assessed in the middle and index fingers using LDF and incremental doses of acetylcholine (ACh) and sodium nitroprusside (SNP). Cutaneous flux data were expressed as cutaneous vascular conductance (CVC). Results: Peak oxygen uptake increased in both exercise groups (p<0.01, d=1.36). ΔtcpO2 demonstrated an increase in the arm cranking group only, with a large effect, but found not statistically significant, (p=0.59, d=0.93). Endothelial-dependent vasodilation improvement was greater in the arm cranking (p<0.05, d=1.07) in comparison to other groups. Both exercise groups improved life satisfaction (p<0.001) as well as reduced discomfort and pain due to Raynaud's phenomenon (p<0.05). Digital ulcers and hospitalizations reported in four patients (36%) of the control group and one of them proceeded for amputation. Arm cranking seems to be the preferred mode of exercise for study participants as compared to cycling (p<0.05). No changes were observed in the body composition or the functional ability in both exercise groups compared to the control group. Conclusions: Our results suggest that the arm cranking has the potential to improve the microvascular endothelial function in SSc patients and to prevent digital ulcers and further related complications. Also notably, our recommended training dose (e.g., a 12 week HIIT program, twice per week), appeared to be sufficient and tolerable for this population. Future research should focus on exploring the feasibility of a combined exercise such as aerobic and resistance training by assessing individual's experience and the quality of life in SSc patients. Reference: [1] Ramos SJ, Dalleck LC, Tjonna AE, Beetham KS, Coombes JS. The impact of high intensity interval training versus moderate-intensity continuous training on vascular function: a systematic review and meta-analysis. Sports Medicine2015;45(5):679–92. Available at https://link.springer.com/article/10.1007%2Fs40279-015-0321-z Acknowledgements: This research was supported by Sheffield Hallam University. We would also like to thank the patients who took part in our research study. Disclosure of Interest: None declared